AN INVESTIGATION OF STUDENTS' STRATEGIES IN COMPREHENDING ENGLISH READING MATERIALS :A case study at one Senior High School in Ternate - Ismail, Ade (2011)
This thesis reports students' reading strategies and reasons for using those strategies in comprehending reading materials at one Senior High School in Ternate, North Maluku, Indonesia. This study was conducted to find out the reading strategies most frequently used by high achiever students, middle achiever students and low achiever students. It also investigated the similarities and differences of reading strategies and the students' reasons for using those strategies in comprehending English text. According to Oxford (1990), the strategy consists of direct and indirect strategies. A direct strategy includes memory, cognitive, and compensation strategies while an indirect strategy deals with metacognitive, affective and social strategies. This study utilized a qualitative research design to get deep understanding about reading strategies most frequently used by high, middle, and low achiever students, the similarities and differences of reading strategies, and the students' reasons in using those strategies. The data were taken from two sources namely questionnaire and interview. The data from the questionnaires covered the students' reading strategies and the similarities and differences of reading strategies while the interview data covered students' reasons in employing reading strategies. The analysis of the data from questionnaires indicated that high achiever students most frequently used cognitive strategies followed by metacognitive, memory, compensation, affective and social reading strategies. The middle achiever students most frequently used cognitive strategies followed by metacognitive, affective, social, and memory strategies while the low achiever students most frequently used cognitive strategies followed by social, metacognitive and affective strategies. The result of the study also indicated that there were 11 similarities of reading strategies which were employed by the different level of students (high, middle, and low achiever students) in different context to create/construct a context, social interaction, and as a form of self-improvement. The data from the interview revealed that all the students used reading strategies to understand a text however the low achiever students employed those strategies to do the exercises which were given by their English teacher. Based on the findings, this study recommends that the English teacher should encourage the low achiever students to employ reading strategies most frequently used by high achiever students. For the further study, the researcher should consider on how to apply those reading strategies in improving the low achiever students' achievement and the relationship between reading strategies and reading comprhension. This study also recommends that the government should conduct teacher training and provide reading materials such as: books, magazine and newspaper in English to motivate the students in doing reading activities and increase their reading skills.